Mediating Role of Job Satisfaction in the Nexus between Career Development and Unprofessional Engagement among Civil Servants in Nepal - Kathayat, Bhupal Bikram (KMC Journal, 2024)
This study aims to investigate the relationships between career development (CrD), job satisfaction (JbS), and unprofessional behaviour (UpE) in public institutions. Employing a causal-comparative research design, it also examines how job satisfaction mediates the CrD-UpE connection among civil servants in Nepal. Utilizing a quantitative approach and convenience sampling, the study includes 385 civil servants from various government organizations. Data validity and reliability were assessed, and analysis was conducted using SPSS 20 and AMOS 22, including structural equation modeling (SEM). The findings confirm positive links between CrD and JbS and CrD and UpE. Additionally, they underscore the role of JbS in mitigating UpE, highlighting the value of investing in career development to enhance job satisfaction and reduce unprofessional behaviour, particularly among Nepalese civil servants. The study emphasizes the robustness of these relationships and offers practical insights for enhancing career development programmes and fostering employee job satisfaction to minimize unprofessional conduct in public organizations.